A developing context: Evaluation and FedNor's evolving institutional context. (16th November 2016) - Sharaput, Markus
Abstract: Context matters when understanding evaluation. This case study illustrates how the internal dynamics of the Federal Economic Development Initiative for Northern Ontario (FedNor) since 2008 were affected by evaluation priorities. Recent changes meant evaluation of FedNor programs focused on indicators of short‐term growth. This prompted a range of adaptive responses by actors within FedNor concerned with securing its developmental mandate, while meeting the requirements of evaluation.